2018
DOI: 10.1590/2318-0331.0318170057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the longitudinal distribution of pressures near the ends of the vertical and horizontal faces in stepped spillway of slope 1V: 0.75H

Abstract: Stepped spillways have been widely used for flood runoff due to of their constructive advantages and in regards to energy dissipation during the drop, allowing downstream dissipation structures to be designed in smaller dimensions. Due to the need for further studies on the effect of runoff in the chute of the stepped spillway and the analysis of dimensionless numbers used to characterize the longitudinal distribution of the pressures acting on the faces of the steps of a spillway, this study aims to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Pressure measurements on the vertical faces of the steps were performed using piezoresistive sensors (Omega PX419, Sitron SP96 and Hytronic TM25 The pressure behavior was evaluated based on the results of extreme pressures with non-exceedance probability of 5%, 1% and 0.1% (P 5% , P 1% and P 0.1% ) on the vertical faces of the steps. Similar statistical parameters of extreme pressures were used by Sánchez-Juny et al (2007,2008) and Osmar et al (2018). It was chosen to analyze only minimum extreme pressures on the vertical face due to the conclusions of Sánchez-Juny et al (2007).…”
Section: /12mentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure measurements on the vertical faces of the steps were performed using piezoresistive sensors (Omega PX419, Sitron SP96 and Hytronic TM25 The pressure behavior was evaluated based on the results of extreme pressures with non-exceedance probability of 5%, 1% and 0.1% (P 5% , P 1% and P 0.1% ) on the vertical faces of the steps. Similar statistical parameters of extreme pressures were used by Sánchez-Juny et al (2007,2008) and Osmar et al (2018). It was chosen to analyze only minimum extreme pressures on the vertical face due to the conclusions of Sánchez-Juny et al (2007).…”
Section: /12mentioning
confidence: 99%
“…Even though, in practical cases, stepped spillways have already been subject to notable floods without showing damage on the chute (Matos & Meireles, 2014;Chanson, 2015), the design practice usually restricts the specific design discharges to values in the order of 15 to 30 m 2 /s, as recommended by Pfister et al (2006a) and Amador et al (2009). Such recommendations are based on the understanding that stepped chutes are more prone to cavitation, when compared to smooth chutes, due to (i) the irregularities created by the steps protruding into the flow (Terrier, 2016) and (ii) the negative pressures that occur, especially, on the vertical faces of the steps, according to contributions of Sánchez-Juny And Dolz (2005), Sánchez-Juny et al (2007), Osmar et al (2018), Ferla et al (2019) and Marques et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on stepped spillways were developed to understand the flow behavior and hydrodynamic efforts that occur along the stepped chute, such as the studies published by Povh et al (2004), Sánchez-Juny et al (2007, 2008, Arantes et al (2009), Takahashi & Ohtsu (2012), Conterato et al (2015), Estrella et al (2015), Xu et al (2015), Dai Prá et al (2016), Zhang & Chanson (2016, 2017, Osmar et al (2018) and Nóbrega et al (2020). Based on the knowledge of hydrodynamic pressures on the steps, studies found the implementation of stepped spillways to be limited to a range of discharges due to the risk of cavitation damage.…”
Section: Introductionmentioning
confidence: 99%
“…The physical hydraulic structure used in this work is described in Sanagiotto (2003), Sanagiotto & Marques (2008) and Gomes (2006) and is very similar to the structure used in other studies (Conterato, 2011(Conterato, , 2014Conterato et al, 2015;Novakoski et al, 2017aNovakoski et al, , 2017bOsmar et al, 2018), with small differences in the approach channel and the channel downstream of the steps.…”
Section: Methodsmentioning
confidence: 99%